Total Quality Management practices: A comparison study between Halal and Non-Halal food producer in Malaysia - Wan Mohamed Radzi, C.W.J.; Manap, N.A.; Jenatabadi, H.S. (2017)
This research aims to empirically compare the multidimensionality of total quality management and its impact firm sustainability in the halal and non-halal food manufacturing in Malaysia. Based on existing studies, we consider six scopes total quality management include strategic planning, leadership, customer focus, human resource management, process management and information and analysis grounded in Malcolm Baldrige National Quality Award benchmarks and three modules of firm sustainability performance contains financial performance, Marketing performance, and partnership performance were acknowledged. Total sample size is 80 operational individual were selected from the halal and non-halal food manufacturing sectors that have or planning to have the ISO 9001 :2000 authorization. Descriptive statistics and partial least square procedures were applied to assessment the research framework. Outcome of the current cross sectional research shows significant difference with respect to the forming of total quality management and impact of it on firm sustainability performance between halal and non-halal food manufacturing sectors. Basically, this study can be applied by halal policy and decision makers in halal food industry, researchers in halal studies, and master & PhD students.